Puno peasants and daily resistance. 1900-1930 - Calisto, Marcela (1991)
In the historiography of southern Peru, peasants have appeared on the scene and played an active role generally when structural factors led them to rebel against the forces that oppressed them. In most of the existing literature, they have been reduced to a secondary level, which is why we know little about the role played by the peasantry in the development and historical conformation of southern Peru. In an attempt to incorporate the peasants in the historical analysis, we want here to deal with the issue of peasant resistance, but not focusing on rebellions, but on daily actions of resistance, understood as confrontational actions that are not extremely violent and, in general, sporadic. and spatially isolated.